Physician - patient communication style and the patient’s motivation to comply with the health care recommendations - Hulewska, Aleksandra; Ziarko, Michał (Studia Psychologica: Theoria et praxis, 2013)
An increasing number of researchers indicate that communications between doctors and patients signihcantly affect the process of treatment. The aim of the present study was to investigate the effects of the type of physicians’ communication style on the patient’s motivation to compliance with the medical recommendations following the end of hospitalization. Thirty hospitalized patients took part in the study. They were asked to fill out questionnaires measuring the following groups of variables: doctor - patient communication style, level of positive and negative affect experienced during hospitalization, level of confidence in physicians, the assessment of medical services quality, and level of motivation to compliance with doctors’ recommendations after leaving hospital. Data were analyzed by means of correlation coefficient and regression analysis. The obtained results suggest that the level motivation to compliance with doctors’ recommendations is correlated with two communication styles named as: (1) personal-nonmedical (r = 0,51; p < 0,01) and (2) personal-medical (r = 0,40; p < 0,05). Besides, the results indicated that the motivation to comply with the recommendations is importantly linked to factors such as: trusting doctors (r = 0,50; p < 0,01) and satisfaction with medical services (r = 0,45; p < 0,05). The regression analysis showed that the level of motivation to compliance with doctors’ recommendations after leaving hospital depends on personal-nonmedical style of communication (5 = 0,51; t = 3,11; p < 0,01) in 25% (R2 = 0,26; F = 9,66; p < 0,01). The results suggest that patients’ motivation to follow the doctors’ recommendations is the highest when the physician communicates with them in the personal-nonmedical style. The research also demonstrated that physicians need to develop their communication skills, especially their nonmedical aspect.